Significance of Platinum‐Based Chemotherapy With Programmed Death‐1 Blockade in Limited Disease Small Cell Lung Cancer: A Retrospective Study - Ayako Shiono; Hisao Imai; Kyoichi Kaira; Takanori Abe; Yuki Sato; Ken Yamamoto; Hiroki Watanabe; Yuko Tsuchiya‐Kawano; Akihiro Tamiya; Takashi Osaki; Noriko Yanagitani; Shigeru Tanzawa; et al. (Thoracic Cancer)
ABSTRACT Main Problem The efficacy and safety of platinum‐based chemotherapy with programmed death‐1 (PD‐1) blockade after chemoradiotherapy (CRT) for the treatment of limited disease (LD) small cell lung cancer (SCLC) is unknown. This study aimed to assess the effectiveness and tolerability of platinum‐based chemotherapy with PD‐1 blockade in patients with recurrent LD‐SCLC after CRT. Methods This retrospective study analyzed 66 patients who experienced recurrence after CRT for LD‐SCLC and received platinum‐based chemotherapy with PD‐1 blockade therapy between August 2019 and September 2020 at 19 Japanese institutions. Clinical efficacy was assessed according to response rate, survival, and toxicity. Results The overall response rate was 53.0% (95% confidence interval [CI], 48.9–65.0), and the disease control rate was 78.7% (95% CI, 68.9–88.5). The median progression‐free survival and overall survival periods were 5.9 (95% CI, 4.7–7.3) months and 24.9 (95% CI, 16.8–28.1) months, respectively. The frequencies of grade ≥ 3 hematological adverse events were as follows: leukopenia, 47.0%; neutropenia, 65.2%; and febrile neutropenia, 8.3%. There was no treatment‐related death. Conclusions Chemoimmunotherapy is a feasible and effective treatment for recurrent disease after CRT in patients with LD‐SCLC, providing a new potential option for the pharmacological management of these patients.